Early Childhood Educators' Perspectives on the Impact of COVID-19 on Child Care - Pic, Annette; Han, Myae; Whitaker, Anamarie; Barnes, Tia Navelene (Social Education Research, 2023)
Recent research documents early care and education (ECE) changes that occurred at the program level (e.g., staffing, enrollment) due to state policies enacted in response to the COVID-19 pandemic; however, less is known about how practices and instruction at classroom level changed. Our study sought to explore ECE educators’ perceptions of how state policies and the pandemic influenced their daily practice and instruction during the pandemic. We conducted in-depth interviews with 12 ECE educators (6 center-based and 6 home-based) selected from a larger survey study from a mid-Atlantic state. Findings revealed there were: 1) significant disruptions with daily routines, family and child interactions, and child assessments; 2) extensive changes in materials used, the room/setting, and instruction; and 3) challenges beyond the classroom such as financial stress, and educator well-being. Results from our study can help inform professional learning experiences and ECE system leaders on where challenges with instruction exist and how the pandemic may have changed educator practices.